THE ROLE EDUCATION TEACHERS IN INSTILLING MODERATION IN ELEMENTARY SCHOOL STUDENTS IN THE DIGITAL ERA - Eri Dwi Cahyanti; Hamidullah Ibda; Ahmad Aji Pangestu; Soimatul Khomisah (Proceeding of International Conference of Islamic Education, 2025)
This article provides a comprehensive analysis of the role of Islamic Religious Education (PAI) teachers in fostering religious moderation among elementary school students in the digital era. The study aims to explore the strategies, challenges, and impacts experienced by teachers in cultivating attitudes of tolerance, inclusivity, and harmony amidst the rapid flow of digital information. Employing a qualitative methodology, data were collected through literature review, interviews, observations, and document analysis. The data were analyzed using the Miles and Huberman model and content analysis to identify patterns in teacher roles and innovations. The findings reveal that PAI teachers serve as role models, facilitators, and innovators by integrating religious moderation values into the curriculum, promoting dialogic learning, and utilizing digital technologies such as interactive media and online platforms. Strategies include strengthening multicultural education, character development, and collaboration with families and communities. However, teachers face challenges such as limited resources, insufficient digital training, resistance to change, and social environmental influences. The study concludes that the success of instilling religious moderation is significantly influenced by teachers’ ability to adapt to technology, innovate in teaching, and receive support from various stakeholders to create an inclusive and harmonious school environment.